Agronomic Characters and Traits Correlation of Iranian Purified Melon Populations in Cold and Dry conditions - Sobhani, Alireza (Asian Journal of Biological and Life Sciences, 2017)
In order to compare eighteen different melon genotypes belonging to two different populations, a two-year field experiment was carried in Khorasan-Razavi Research Centre for Agriculture and Natural Resources based on randomized complete blocks design with three replicates. The results indicated that selection and purification could improve studied traits. For instance, fruit yield, fruit weight and fruit number as well as sugar percentage and flesh thickness increased in purified genotypes. In addition, skin thickness and cavity dimeter decreased in purified genotypes. The maximum fruit yield (26.93 ton ha-1) was related to Khatooni genotype, which is the most important cultivated genotype in Khorasan-Razavi province. By contrast the minimum yield was obtained from native Sooski genotype. Among exotic genotypes, purified Jajoo showed the best results. Fruit sugar percentage differ from 11.5 to 14.67 in different genotypes. The results showed that selection could improve fruit sugar percentage in some genotypes. The maximum fruit sugar percentage was recorded in purified Dargazi genotype, however native Dargazi was better than other genotypes. According to the cluster analysis the melon genotypes were divided into three different groups. The first group consist of seven genotypes i.e. Shadgan, purified Shadgan, Ananas, Khaghani, purified Sooski, Akila and Chah-Paliz. The second group consist of purified Khagani, purified Chah-Paliz, Jajoo, Khatooni and Dargazi and the third group consist of purified Chah-Paliz, purified Jajoo, native Bandi, purified Bandi and purified Khatooni.
Keywords: Cluster; Factor analysis; Purified population; Sugar percentage; Yield